2019
DOI: 10.1016/j.amc.2019.06.059
|View full text |Cite
|
Sign up to set email alerts
|

A Monte Carlo method for computing the action of a matrix exponential on a vector

Abstract: A Monte Carlo method for computing the action of a matrix exponential for a certain class of matrices on a vector is proposed. The method is based on generating random paths, which evolve through the indices of the matrix, governed by a given continuous-time Markov chain. The vector solution is computed probabilistically by averaging over a suitable multiplicative functional. This representation extends the existing linear algebra Monte Carlo-based methods, and was used in practice to develop an efficient algo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…Finding a probabilistic representation for this problem requires in practice [7] to use a splitting method for approximating the action of the matrix exponential over the vector u as follows,…”
Section: Probabilistic Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Finding a probabilistic representation for this problem requires in practice [7] to use a splitting method for approximating the action of the matrix exponential over the vector u as follows,…”
Section: Probabilistic Methodsmentioning
confidence: 99%
“…However, in practice this does not occur. Through the analysis of the intersection similarity of several networks [7] it was shown that the chosen value of β does not affect significantly the results, being in all cases the differences well below the typical error tolerances, and even becoming smaller for increasingly larger network sizes. Consequently, and to ensure fast convergence of the method, in the simulations below we have used β = 1/λ max , where λ max is the maximum eigenvalue of A.…”
Section: Concerning the Convection-diffusion Equation Mathematicallymentioning
confidence: 99%
See 3 more Smart Citations